Analysis of The Potential Values of Character Education in The Independent Curriculum on Traditional Arts Typical of The Sasak Tribe of Lombok "Peresean" - Siti Rabiatul Fajri; Titi Laily Hajiriah; Herdiyana Fitriani; I Putu Sriartha; I Wayan Mudana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to explore in more depth the potential values of character education contained in the traditional art of "Peresean" of the Sasak tribe in Lombok, with a focus on the implementation of the Merdeka Curriculum. The research approach used is qualitative research with ethnography methods. Data collection techniques use observation, interviews and documentation. The subjects in this study are traditional leaders, community leaders and religious leaders in 6 traditional villages on Lombok Island. Data analysis using an interactive analysis model which consists of three activity flows that occur simultaneously, namely through data collection, data reduction, data presentation and drawing conclusions/verification. The results showed that the values of character education obtained from the competition were; 1) independence, 2) Faithful, fearful of God Almighty, and noble character, 3) Critical reasoning, 4) Mutual assistance, 5) Global diversity, and 6) Creativity. While the values of character education formed in awiq-awiq peresean are: 1) Independent, 2) Faith, fear of God Almighty, and noble morals, and 3) Critical reasoning.